Technical Efficiency of Rice Farm Production in Aceh Province, Indonesia - Helmi Noviar; Raja Masbar; Aliasuddin Aliasuddin; Sofyan Syahnur (Proceedings of AICS - Social Sciences, 2018)
The purpose of the present paper is to examine the efficiency of Indonesian rice production conducted in Aceh Province, by using agricultural census data 2013 with a sample of 1,029 characteristics of farm households. The analysis model used is stochastic frontier analysis (SFA)) approach and the estimation result obtained that rice production factors such as wages of farm workers, harvested area, fertilizer, and seeds have not been technically efficient. Furthermore, the economical scale of rice production in Aceh Province is decreasing return to scale that coherent with the results of the efficiency test.Keywords: efficiency, farmer household, stochastic frontier analysis, economic scale.